1997
DOI: 10.1007/s002239900179
|View full text |Cite
|
Sign up to set email alerts
|

Effects of moderate endurance exercise on calcium, parathyroid hormone, and markers of bone metabolism in young women

Abstract: We investigated the short-term (1 hour-3 days) effects of a 45 minute run on calcium, parathyroid hormone, the carboxyterminal propeptide of type I procollagen (PICP), and the immunoactive carboxyterminal telopeptide of type I collagen in serum (ICTP) in young females. Fourteen healthy young women, aged 25.2 +/- 0.6 years (mean +/- SEM) with regular menstruations, participated. The test was outdoor jogging for 45 minutes at an intensity of 50% of VO2 max. Blood samples were collected 15 minutes before the test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
52
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(64 citation statements)
references
References 38 publications
10
52
2
Order By: Relevance
“…This is in contrast to previous studies of high-intensity endurance exercise (29,38) and some (61) but not all (56, 62) studies of low-to moderate-intensity exercise. The decrease in daytime OC concentrations is associated with the nocturnal increase in cortisol that precedes it (30, 45), although we observed no decrease in OC with exercise at 75% V O 2max despite higher cortisol concentrations compared with 55% and 65% V O 2max .…”
Section: Discussioncontrasting
confidence: 99%
“…This is in contrast to previous studies of high-intensity endurance exercise (29,38) and some (61) but not all (56, 62) studies of low-to moderate-intensity exercise. The decrease in daytime OC concentrations is associated with the nocturnal increase in cortisol that precedes it (30, 45), although we observed no decrease in OC with exercise at 75% V O 2max despite higher cortisol concentrations compared with 55% and 65% V O 2max .…”
Section: Discussioncontrasting
confidence: 99%
“…Previous experimental studies have suggested that mechanical loading and PTH have an interactive effect on bone turnover [32] and this interaction may occur during the mechanotransduction [33]. In clinical studies, short bouts of exercise have been found to stimulate transient PTH secretion [14,15,34,35]. Contrary to this, we found a significant decrease in serum PTH in the exercise group compared to the control group at 6 and 12 months while BMD increased and favorable geometric changes occurred.…”
Section: Discussioncontrasting
confidence: 78%
“…Similar to the current study, Thorsen et al, [29] In contrast, Kristoffersson et al, [30] found increased iCa levels after short term maximal work, without significant changes in the serum PTH levels.…”
Section: Discussionsupporting
confidence: 88%